Communication and metacommunication in human development - Branco, Angela Uchoa; Valsiner, Jaan (Emerald Publishing Limited : Information Age Publishing, 2004)
The book is divided into three parts. In Part I, basic conceptual and theoretical issues concerning communication and metacommunication are presented. Part II continues the coverage with the issues of communication and metacommunication. Those are extended as each chapter puts forward new insights and contextualizes them within the realms of teaching- learning processes, early adaptation to nursery school contexts, and of the analysis of processes occurring at a particular dimension of human development (gender identity). Part III provides further conceptual and theoretical elaborations on the phenomena from the unique viewpoints of scholars with diverse backgrounds, which definitely furnish scientific discussion over the issue with fresh and productive ideas. Throughout the chapters, the reader is supplied with empirical projects conducted in different research laboratories, each study granting novel illustrations of methodological approaches to analyze the complexities of communication and metacommunication processes and their relevant constitutive roles in specific contexts.